Vapor-fed solar hydrogen production exceeding 15% efficiency using earth abundant catalysts and anion exchange membrane. Issue 10 (3rd October 2017) - Heremans, Gino; Trompoukis, Christos; Daems, Nick; Bosserez, Tom; Vankelecom, Ivo F. J.; Martens, Johan A.; Rongé, Jan
Abstract : A vapor-fed solar hydrogen generator with KOH-doped poly(vinyl alcohol) anion exchange membrane flanked with NiFe and NiMo catalysts is demonstrated. Abstract : Vapor-fed solar hydrogen generators can convert water vapor from the air into hydrogen using sunlight as the energy source. Hydrogen and oxygen evolution reactions are performed in the gas phase in cathode and anode compartments separated by a membrane. Anion exchange membranes show great promise for this type of solar hydrogen generator. They provide an alkaline environment enabling the use of earth abundant materials as electrocatalysts. In this work, a vapor-fed solar hydrogen generator with KOH-doped poly(vinyl alcohol) anion exchange membrane flanked with NiFe and NiMo catalysts is demonstrated. The device reached an average 15.1% solar-to-hydrogen efficiency at room temperature and 95% relative humidity. This first demonstration of gas phase water splitting with earth abundant catalysts and anion exchange membrane opens a pathway to low cost, autonomous, efficient and safe solar hydrogen generators.